2023
DOI: 10.1136/bmjresp-2023-001726
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled corticosteroids and risk of lower respiratory tract infection withMoraxella catarrhalisin patients with chronic obstructive pulmonary disease

Rikke Helin Johnsen,
Christian Kjer Heerfordt,
Jonas Bredtoft Boel
et al.

Abstract: BackgroundUse of inhaled corticosteroids (ICS) is common in patients with chronic obstructive pulmonary disease (COPD) and has been associated with an increased risk of pneumonia.Moraxella catarrhalisis one of the most common bacterial causes of infectious exacerbation in COPD. Currently, to our knowledge, no studies have investigated if ICS increases the risk of lower respiratory tract infection withM. catarrhalisin patients with COPD.ObjectiveTo investigate if accumulated ICS use in patients with COPD, is as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
2
0
1
Order By: Relevance
“…I flere nyere og større observationsstudier har man påvist en klar sammenhaeng mellem brugen af ICS og risikoen for isolation af såvel H. influenza, M. catarrhalis, S. pneumonia som P. aeruginosa hos patienter med KOL [18][19][20][21]. Derudover er der studier, der har rapporteret, at ICS også er en betydelig risikofaktor for infektion med nontuberkuløse mykobakterier ved KOL [22].…”
Section: Ugeskrift For Laeger Ugeskrift For Laegerunclassified
“…I flere nyere og større observationsstudier har man påvist en klar sammenhaeng mellem brugen af ICS og risikoen for isolation af såvel H. influenza, M. catarrhalis, S. pneumonia som P. aeruginosa hos patienter med KOL [18][19][20][21]. Derudover er der studier, der har rapporteret, at ICS også er en betydelig risikofaktor for infektion med nontuberkuløse mykobakterier ved KOL [22].…”
Section: Ugeskrift For Laeger Ugeskrift For Laegerunclassified
“…Cardiac events are significant complications for LRTI patients, and comorbid chronic heart disease may predispose OSA patients to these events [ 115 ]. Similarly, comorbid COPD is important as these patients often receive corticosteroids, increasing pneumonia risk [ 116 ]. Many studies confirmed OSA as an independent risk factor, often adjusted for chronic diseases as covariates.…”
Section: Obstructive Sleep Apnea and Lower Respiratory Tract Infectio...mentioning
confidence: 99%
“…Long-term use of ICS itself might contribute to potentially deleterious airway microbiota changes by increasing the bacterial load of potentially pathogenic germs. ICS use in COPD subjects has been associated with dose-dependent increased risks of acquiring Haemophilus influenzae [57], Streptococcus pneumoniae [58], Moraxella catarrhalis [59], and Pseudomonas aeruginosa colonization [60]. Leitao et al evaluated the effects of a 12-week treatment with ICS/LABA combination vs. LABA alone on the airway microbiome of stable COPD subjects via bronchoalveolar lavage.…”
Section: Mouth and Upper Airways Disturbances Pneumonia Other Lung In...mentioning
confidence: 99%